Risk Factors for Enterovirus A71 Seropositivity in Rural Indigenous Populations in West Malaysia - Nik Nadia, NMN; Sam, I Ching; Nasibah, Khaidir; Romano, Ngui; Yvonne Ai, Lian Lim; Xiang, Ting Goh; Seow, Huey Choy; Yoke, Fun Chan (PLOS, 2016)
Enterovirus A71 (EV-A71), which is transmitted by the fecal-oral route, causes hand, foot and mouth disease and, rarely, severe neurological complications. In Malaysia, the indigenous rural community (Orang Asli) has a high prevalence of parasitic diseases due to poor sanitation, water supply and hygiene practices. This cross-sectional study compared the seroepidemiology of EV-A71 among rural Orang Asli and urban Kuala Lumpur populations in West Malaysia, and determined the risk factors associated with EV-A71 seropositivity in rural Orang Asli. Seropositive rates were determined by neutralization assay. EV-A71 seropositivity was strongly associated with increasing age in both populations. Rural Orang Asli children 12 years had significantly higher EV-A71 seropositivity rates than urban Kuala Lumpur children (95.5% vs 57.6%, P < 0.001), and also higher rates in the age groups of 1–3, 4–6 and 7–12 years. Multivariate analysis confirmed that age 12 years (adjusted OR 8.1, 95% CI 3.2–20.7, P < 0.001) and using untreated water (adjusted OR 6.2, 95% CI 2.3– 16.6, P < 0.001) were independently associated with EV-A71 seropositivity in the Orang Asli population. Supply of clean drinking water may reduce the risk of EV-A71 infection. With significantly higher EV-A71 seropositive rates, younger rural children should be a priority target for future vaccination programs in Malaysia.